Office Technology and Management Skills and its Challenges in Nigeria - Liman (AMNIM), Tijjani Umar (International Journal of Psychosocial Rehabilitation, 2020)
This paper discussed some of the challenges faced by the Office Technology and Management Skills due to present technological changes globally, today, the technological changes has reformed many professions with a view to meet the current global changes in many areas i.e. higher productivity, speed, accuracy, paperless office and excellent routine office work, packaging. However, all this process cannot be achieved without the use of modern machine is what is called “automation”. At the introduction, the paper defined skill, office technology and management as well as its challenges, unemployment, aspect of office automation, it further highlighted some of the factors that hindered office technology and management skills (graduates). Recommendations was also made on how such challenges can be address. Finally, conclusion was offered for the institution offering the OTM courses to adopt the current global changes so as to restructure their curriculum to meet the global standard and for satisfactory job performances and personal fulfilment in the global labor market